A paradigm for chronic fatigue syndrome: caught between idiopathic intracranial hypertension and spontaneous intracranial hypotension; caused by cranial venous outflow obstruction. Issue 3 (3rd July 2021) - P. Higgins, J Nicholas; Pickard, John D.
ABSTRACT: Background: Clinical similarities between chronic fatigue syndrome and idiopathic intracranial hypertension, supported by measurements of intracranial pressure, invite suggestions that they may be connected, the first representing a mild version of the second. Yet, if this is to be the basis for a structural explanation for chronic fatigue syndrome, it already seems incomplete, failing to explain cases where disability seems disproportionate. Is there some other confounding variable? Purpose: To refine, in this theoretical paper, an earlier model connecting chronic fatigue syndrome with idiopathic intracranial hypertension to allow for a cerebrospinal fluid (CSF) leak. Model: In this model, the primary structural problem is acquired obstruction to cranial venous outflow. This obstruction can take different forms, may be intermittent and subtle, and even be mistaken for normal venous anatomy, yet would be the driving force behind a tendency towards increased intracranial pressure. This chronic elevation of intracranial pressure stresses the dural membrane maintaining the integrity of the subarachnoid space, which can rupture at a weak point, allowing CSF to leak away and intracranial pressure to fall. The clinical manifestation of this disorder is the product of the severity of cranial venous outflow compromise and of the competing forces on intracranial pressure. In some instances, a CSF leak will mitigate the effects of venous compromise, in others it will compound it, producing a disease spectrum ranging through idiopathic intracranial hypertension, chronic fatigue syndrome, fibromyalgia, and spontaneous intracranial hypotension. Conclusion: In chronic fatigue syndrome a normal intracranial pressure does not exclude significant physiological disturbance.